Statement by the OEGGG with Review of the Literature on the Mode of Delivery of Premature Infants at the Limit of Viability - Fischer, Thorsten; Mörtl, Manfred; Reif, Philipp; Kiss, Herbert; Lang, Uwe; for the Austrian Society for Gynaecology and Obstetrics (OEGGG) (Geburtshilfe und Frauenheilkunde, 2018)
In 2017, the Austrian Society for Paediatric and Adolescent Medicine (ÖGKJ) published a guideline on the primary care of premature infants at the limit of viability. In this guideline, it is recommended that a Caesarean section be preferred as mode of delivery with regard to an early preterm birth (22 + 0 – 24 + 6 weeks of pregnancy) due to an allegedly lower perinatal risk of cerebral haemorrhage. In contrast to this, the Austrian Society for Gynaecology and Obstetrics (OEGGG) considers there to be no clinical and scientific basis for this recommendation and the mode of delivery in the case of early preterm birth must be adapted to the individual maternal and foetal clinical situation. The international data available from the generally retrospective investigations show heterogeneous results regarding the mode of delivery. The prospective and randomised data in this regard are insufficient. A Cochrane analysis does not show any advantage in favour of a Caesarean delivery. The German-language guidelines (AWMF and Switzerland) make analogous recommendations for adapting the mode of delivery with regard to an early preterm birth individually to the respective clinical situation. In the case of an early preterm birth and a singleton in cephalic presentation, the OEGGG therefore recommends individual management of the delivery which takes the maternal and foetal clinical situation into account and also includes vaginal delivery as a mode of delivery in the clinical decision process.Im Jahr 2017 hat die Österreichische Gesellschaft für Kinder- und Jugendheilkunde (ÖGKJ) eine Leitlinie zur Erstversorgung von Frühgeborenen an der Grenze der Lebensfähigkeit veröffentlicht. In dieser Leitlinie wurde empfohlen, im Bereich der frühen Frühgeburt (22 + 0 – 24 + 6 SSW) aufgrund eines vermeintlich geringeren perinatalen Hirnblutungsrisikos als Entbindungsmodus eine Sectio caesarea zu präferieren. Im Gegensatz dazu ist die Österreichische Gesellschaft für Gynäkologie und Geburtshilfe (OEGGG) der Ansicht, dass es für diese Empfehlung keine klinische und wissenschaftliche Grundlage gibt und der Entbindungsmodus im Bereich der frühen Frühgeburtlichkeit der individuellen maternalen und fetalen klinischen Situation angepasst werden muss. Die internationale Datenlage der meist retrospektiven Untersuchungen zeigt heterogene Ergebnisse zu der Fragestellung des Entbindungsmodus. Prospektive und randomisierte Daten liegen nur unzureichend vor. Eine Cochrane-Analyse zeigt keinen Vorteil zugunsten der Schnittentbindung. Die deutschsprachigen Leitlinien (AWMF und Schweiz) kommen zu analogen Empfehlungen, den Entbindungsmodus im Bereich der frühen Frühgeburt individuell der jeweiligen klinischen Situation anzupassen. Die OEGGG empfiehlt deshalb im Bereich der frühen Frühgeburtlichkeit bei Einlingen in Schädellage ein individuelles Entbindungsmanagement, das die maternale und fetale klinische Situation berücksichtigt und auch eine Vaginalgeburt als Geburtsmodus in den klinischen Entscheidungsprozess einschließt.
Keywords: mode of delivery; early preterm birth; pregnancy; perinatal mortality; neonatal morbidity